An update on the distribution and morphology of Ixora amplexifolia (Ixoroideae, Rubiaceae) in Papua New Guinea - Maraia, Heveakore; Orsak, Larry; Gideon, Osia; Okpul, Tom (Phytotaxa, 2019)
Ixora amplexifolia (Ixoroideae, Rubiaceae), belongs to subgenus Sathroclamys, section Hypsophyllum. It is endemic to the northern part of Papua New Guinea (PNG). This paper updates the morphological description of the species to incorporate new fruit data, and review its alignment with its cohorts of section Hypsophyllum and their distribution in PNG.